Long term observation of MRSA prevalence in a German rehabilitation center: risk factors and variability of colonization rate - Gieffers, Jens; Ahuja, André; Giemulla, Ronald (German Medical Science GMS Publishing House, 2016)
Background: Data on MRSA prevalence in rehabilitation centers are sparse.Methods: We screened more than 18,000 patients with neurological, cardiac/pulmonary or orthopedic diagnoses treated in three German rehabilitation centers and documented potential risk factors in almost 1,500 of them.Results: 2.1% were MRSA positive (CI 1.9%-2.4%). Prevalence was higher in neurologic patients (3.7%) and lower in orthopedic patients (0.9%). While the overall MRSA situation was stable over two years, the weekly MRSA rate fluctuated strongly (0.0% to 8.0%). We confirmed five risk factors in our study population. A risk adapted screening strategy derived from our data had a significance of 74% and a positive predictive value of only 2.2%.Conclusion: MRSA positivity is a rare and highly variable event, requiring a huge sample size to generate robust data. The benefit of a risk-adapted screening strategy over a general screening should be questioned in each individual setting.